2023
DOI: 10.3390/app13053217
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in H2S Removal from Gas Streams

Francisco Jose Alguacil

Abstract: Hydrogen sulfide is a toxic and corrosive gas; thus, in order to mitigate its environmental impact, its capture and removal from various emitting sources, natural and anthropogenic, is of a necessity. In this work, recent advances (2020–2022) proposed by a series of investigations are reviewed. Adsorption using metal-oxide-based adsorbents appeared to be the most popular technology, whereas solvent absorption is used to co-absorb both toxic H2S and CO2. The uses of the various membrane technologies for H2S rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…The existing widespread desulfurization techniques [8][9][10][11] are absorption (usually chemical scrubbing using sodium hydroxide), adsorption [12], membrane filtration and biofiltration [13], mostly on biotrickling filters (BTF). A life cycle assessment of desulfurization techniques comparing biological filtration, chemical scrubbing and adsorption on impregnated activated carbon (AC) demonstrated that BTFs are more favorable in terms of environmental impact compared to other techniques, with chemical scrubbing being the worst technique [14].…”
Section: Introductionmentioning
confidence: 99%
“…The existing widespread desulfurization techniques [8][9][10][11] are absorption (usually chemical scrubbing using sodium hydroxide), adsorption [12], membrane filtration and biofiltration [13], mostly on biotrickling filters (BTF). A life cycle assessment of desulfurization techniques comparing biological filtration, chemical scrubbing and adsorption on impregnated activated carbon (AC) demonstrated that BTFs are more favorable in terms of environmental impact compared to other techniques, with chemical scrubbing being the worst technique [14].…”
Section: Introductionmentioning
confidence: 99%